2003
DOI: 10.1002/polb.10678
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the 1030‐cm−1 band of poly(ethylene terephthalate) fibers using polarized raman microscopy

Abstract: Polarized Raman spectroscopy was used to analyze uniaxially oriented fibers of poly(ethylene terephthalate) (PET) fibers. The second‐order and fourth‐order Legendre polynomials of the orientation distribution function of the 1030‐cm−1 vibrational band were determined to be zero for samples of low‐to‐moderate orientation. Because this band was assigned to the gauche conformation of the ethylene glycol unit, the orientation of the gauche configuration of ethylene glycol units in PET for PET of low‐to‐moderate or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
(24 reference statements)
1
6
0
Order By: Relevance
“…These results suggest that the gauche conformers are essentially isotropic and that their fraction decreases with the overall orientation of the system. Similar behaviors were observed by Adar and Noether and by Yang and Michelson , in their studies of spin-oriented PET fibers.…”
Section: Resultssupporting
confidence: 87%
“…These results suggest that the gauche conformers are essentially isotropic and that their fraction decreases with the overall orientation of the system. Similar behaviors were observed by Adar and Noether and by Yang and Michelson , in their studies of spin-oriented PET fibers.…”
Section: Resultssupporting
confidence: 87%
“…21,23 Briefly, it was found that the instrumental factor decreases with the increase of wavenumber in the Raman shift. The depolarization ratio for chemicals with known depolarization ratios for specific bands, butyl benzoate, 2-butanone, CCl 4 , and amorphous PET, were determined.…”
Section: Resultsmentioning
confidence: 99%
“…Higher order parameters (i.e., P 6 , P 8 ,...) are discarded since they typically have decreasing contributions, while odd order parameters vanish because of fiber symmetry. Our proposed approach is partly based on the complete (tilt) method, which includes an additional measurement with a tilted fiber. ,, More precisely, Raman intensities must be measured at different experimental configurations as described below In the notation I ij BS (β) used through eqs –, BS refers to laser backscattering in the x 2 direction in Figures and , the subscripts i and j refer to the polarization of the analyzer ( i ) and of the incident light ( j ), and β is the tilting angle of the fiber in the x 1 – x 3 plane. The summation is intended to be overall molecules captured within the focal volume of the incident laser, and the α values are the Raman tensor coefficients.…”
Section: Theorymentioning
confidence: 99%
“…Five independent spectra using the 785 nm excitation line were collected in the I 33 BS (0), I 33 BS (90), I 31 BS (0), and I 31 BS (45) configurations, while an additional spectrum for normalization purposes was also collected in the I 31 BS (90) configuration. The instrumental factor of the depolarization ratio F (ν) was determined using butyl benzoate, 2-butanone, and CCl 4 as reference materials, proposed by Yang and Michielsen. , Normalization of the measured integrated intensity is described by The superscripts meas and approx are the measured and approximated intensities, respectively. The 1000–1200 cm –1 spectral region was analyzed using Igor software v6.37, fitting the experimentally measured spectra with Gaussian functions and a linear background.…”
Section: Experimental Aspectsmentioning
confidence: 99%